Cognitive Abilities and the Demand for Bad Policy - Salvatore Nunnari; Eugenio Proto; Aldo Rustichini (Institute of Labor Economics (IZA), 2024)
Rational choice theories assume that voters accurately assess the outcomes of policies. However, many important policies—such as regulating prices and introducing Pigouvian taxation—yield outcomes through indirect or equilibrium effects that may differ from their direct effects. Citizens may underestimate these effects, leading to a demand for bad policy, that is, opposition to reforms that would increase welfare or support for reforms that would decrease it. This appreciation might be linked to cognitive functions, raising important research questions: Do cognitive abilities influence how individuals form preferences regarding policies, especially untried reforms? If so, what is the underlying mechanism? We use a simple theoretical framework and an experiment to show that enhanced cognitive abilities may lead to better policy choices. Moreover, we emphasize the crucial role of beliefs about other citizens' cognitive abilities. These findings have important policy implications as they suggest that educational programs developing cognitive skills or interventions increasing trust in others' understanding could improve the quality of democratic decision-making in our societies.
Keywords: C90; D72; D91; 330; voting; policy reform; political failure; cognition; experiment